2020
DOI: 10.3201/eid2608.191214
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dengue Virus and Leptospira Co-Infections with Malaria Severity

Abstract: I n tropical countries, including India, acute febrile illnesses (AFIs) constitute a group of infections with similar manifestations, such as fever, malaise, body aches, chills, hepatic and renal dysfunction, and central nervous system effects. The causative agents of AFI can be bacterial (e.g., Orientia tsutsugamushi, Leptospira, and Salmonella enterica serovar Typhi), parasitic (protozoans of the apicomplexa family), or viral (e.g., dengue virus [DENV], chikungunya virus [CHIKV], influenza A[H1N1] virus) (1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 39 publications
0
33
4
Order By: Relevance
“…To the best of our knowledge, there are no reports about the interactions of these pathogens in coinfections in Venezuela, despite multiple infections may complicate malaria and lead to failure when it comes to treatment responsiveness. High prevalence of malaria coinfection was found in this study (34.2%), even higher than reported in Brazil (20%) [25]; but lower than that found in a recent study in India (60%) [29]. Thus, physicians should be suspicious of coinfection in malaria cases with inadequate treatment response or atypical manifestations.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…To the best of our knowledge, there are no reports about the interactions of these pathogens in coinfections in Venezuela, despite multiple infections may complicate malaria and lead to failure when it comes to treatment responsiveness. High prevalence of malaria coinfection was found in this study (34.2%), even higher than reported in Brazil (20%) [25]; but lower than that found in a recent study in India (60%) [29]. Thus, physicians should be suspicious of coinfection in malaria cases with inadequate treatment response or atypical manifestations.…”
Section: Discussioncontrasting
confidence: 70%
“…A study in Peru indicated Plasmodium/DENV coinfection was not associated with worse disease [26], similar to another study in India were the coinfection with DENV serotype 4 (DENV-4), even was associated with mild malaria. [29]. Differences in DENV serotypes or Plasmodium spp may explain the differences of the results.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Malaria diagnosis in the present study using microscopy and antigen detection using RDTs may underestimate the proportion of falciparum malaria cases among febrile patients, which can lead to inadequate detection of malaria as a mono- or co-infection as shown by recently published literature [ 37 40 ]. Therefore, the findings of this study should be interpreted cautiously in this context, and the underestimation of malaria in mono- and co-infected febrile patients could not be ruled out.…”
Section: Discussionmentioning
confidence: 85%
“…Of the 125 articles examined for full text, 111 articles were excluded for the following reasons: 55 had no data on co-infection of malaria and leptospirosis, 25 had no malaria cases, 13 were review articles, 9 were case reports or case series for malaria and leptospirosis, and 9 had no leptospirosis cases. Fourteen articles [ 26 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] met the eligibility criteria and were included in the qualitative synthesis. Additional searches on reference lists and Google Scholar found one article [ 42 ].…”
Section: Resultsmentioning
confidence: 99%